A case study: promotional mix used in increasing sales of Pennzoil Platinum Semi Synhetic Lubricant / Raja Arif Iskandar Raja Yahaya Aziz - Raja Yahaya Aziz, Raja Arif Iskandar (2011)
In the real business world today, majority of the company realized the significant importance of the promotional mix and sales promotion to increase the sales. As a consequence the marketing department is aggressively doing the promotional mix to enhance the brand name. The UMW Pennzoil Sdn Bhd is a company that produced many type of lubricant in full range of product such as Passenger Car Motor oil, Motor Cycle oil, Diesel Engine Oil, Gear and Transmission oil and Greases. The lubricant industry in Malaysia is more likely to be influenced by the product quality and brand name that drives the customer to meet their expectation. The company should focus more in gaining the brand awareness through the effective and efficient promotion mix. High brand awareness among the customer can produce better result and become the choice of customer that can be interpreted in the sales number.